Pelatihan Pembuatan Lilin Aromaterapi dari Minyak Jelantah untuk Peningkatan Kreativitas dan Kemandirian Ekonomi Ibu-Ibu PKH - Mataram, Sayid; Firmansyah, Raihan Ady; Ghaida, Nabila; Putri, Ranita Mulansari; Karunia, Putri Lya; Afifah, Dinda; Utami, Dian Fitri; Ajrina, Salsa Billa; Puspitasari, Ita; Hikmah, Nur; Alfiandari, Dwy Putri (Yayasan Daarul Huda Kruengmane, 2025)
Crude oil is one of the household wastes that are often disposed haphazardly without adequate management thus posing environmental pollution and impacting public health. On the other hand, this waste has the potential to be processed into selling-value products, one of which is aromatherapy candles. The market need for aromatherapy candles is relatively high, both for decorative and relaxation needs, so the utilization of safflower oil as a basic ingredient of candle making could be an opportunity for community creative economic empowerment. The March Eleventh University Real Work Tuition (KKN) program was implemented in Krikilan Village, Kalijambe District, Sragen County, with the aim of improving the skills of mothers of Hope Family Program (WHO) beneficiaries through basic roadside aromatherapy candle making training. This activity uses the methods of extension, demonstration, live practice, as well as accompaniment. Activity participants numbered 30 housewives who participated actively in the whole training series. Training results showed a significant improvement in the aspects of knowledge regarding the environmental impact of crude oil, technical skills of wax manufacturing, as well as understanding regarding the economic potential of the product. The resulting aromatherapy wax products have marketable aesthetic qualities and fragrances, thus opening up opportunities for household-based small businesses. Additionally, these activities impact on increasing participants’ sense of self-confidence and social solidarity, which is an important capital in building economic self-reliance. The program proves that a creative skills-based empowerment approach can be an innovative solution in waste management as well as improving community well-being.